An acceptable slow-release phosphate preparation 'Slow P'. Issue 537 (July 1970) - Parsons, Victor; Porter, Andrew; Parsons, Valerie; Lund, Christopher
Abstract : Slow P has been an acceptable form of oral phosphate therapy in a series of patients with a variety of bone disease. Therapeutic responses have been achieved in a number of patients without side effects together with minor elevation of the serum and urinary phosphate in the majority of patients. Some patients have continued with such supplements for several months which encourages an extended trial under more stringent conditions.